Renewable decyl-alcohol templated synthesis of Si-Cu core-shell nanocomposite - Salim M.A.; Misran H.; Othman S.Z.; Shah N.N.H.; Razak N.A.A.; Manap A. (Institute of Physics Publishing, 2023)
Monodispersed silica spheres with particles size of ca. 450 nm were successfully synthesized using a modified Stber method. The synthesized monodispersed silica spheres were successfully coated with copper using modified sol-gel method employing nonsurfactant surface modifiers and catalyst. A renewable palm oil based decyl-alcohol (C10) as nonsurfactant surface modifiers and catalyst were used to modify the silica surfaces prior to coating with copper. The X-ray diffraction patterns of Si-Cu core-shell exhibited a broad peak corresponding to amorphous silica networks and monoclinic CuO phase. It was found that samples modified in the presence of 1 ml catalyst exhibited homogeneous deposition. The surface area of core materials (SiO2) was at ca. 7.04 m2/g and Si-Cu core-shell was at ca. 8.21 m2/g. The band gap of samples prepared with and without catalyst was calculated to be ca. 2.45 eV and ca. 3.90 eV respectively based on the UV-vis absorption spectrum of the product. Published under licence by IOP Publishing Ltd.